Rare variants and de novo variants in mesial temporal lobe epilepsy with hippocampal sclerosis. (June 2018) - Wong, John K.L.; Gui, Hongsheng; Kwok, Maxwell; Ng, Ping Wing; Lui, Colin H.T.; Baum, Larry; Sham, Pak Chung; Kwan, Patrick; Cherny, Stacey S.
Abstract : Objective: We investigated the role of rare genetic variants and of de novo variants in the pathogenesis of mesial temporal lobe epilepsy related to hippocampal sclerosis (MTLE-HS). Methods: Whole-exome sequencing (WES) was performed in patients with MTLE-HS and their unaffected parents (trios). Genes or gene sets that were enriched with predicted damaging rare variants in the patients as compared to population controls were identified. Patients and their parents were compared to identify whether the variants were de novo or inherited. Results: After quality control, WES data from 47 patients (26 female), including 23 complete trios, were available for analysis. Compared with population controls, significant enrichment of rare variants was observed in SEC24B . Integration of gene set data describing neuronal functions and psychiatric disorders showed enrichment signal on fragile X mental retardation protein (FMRP) targets. Twenty-one de novo variants were identified, with many known to cause neuropsychiatric disorders. The FMRP-targeted genes also carried more de novo variants. Inherited compound heterozygous and homozygous variants were identified. Conclusions: The genetic architecture underlying MTHE-HS is complex. Multiple genes carrying de novo variants and rare variants among FMRP targets were identified, suggesting a pathogenic role. MTLE-HS and other neuropsychiatric disorders may have shared biology.